Quantificação e caracterização de óleo microbiano produzido por linhagens de Yarrowia lipolytica utilizando glicerol como fonte de carbono - Elisa Duarte Guerra Coelho (2018)
Oleaginous microorganisms are capable of producing at least 20% of its dry weight in the form of lipids, which many times have fatty acid compositions similar to the plants used in the production of 1st generation biodiesel. Oleaginous yeasts are capable of producing oil from hydrofobic substrates, glucose or glycerol, which is a residue from the biodiesel industry and not valorized in the market. Yarrowia lipolytica is able to degrade glycerol and it is considered a model species for lipid accumulation. Besides that, its metabolism and genome are better known than other species. Different yeast strains and cultivation conditions can result in different lipid ammounts and fatty acid profiles. Thus, in this work five Y. lipolytica strains were tested for microbial oil production, from pure glycerol, at 15 e 25°C. Any isolate was considered oleaginous at 15 ºC, while at 25 ºC the srains UFMG-CM-Y6114 (isolated from chese), UFMG-CM-Y4187 (from Paraná sand beach) e UFMG-CM-Y6189 (isolated from Antactica) produced more than 20% of lipid content (29,30%, 26,95% and 34,38%, respectively). Strains UFMG-CM-Y6114 and UFMG-CM-Y4187 showed no significant diference in relation to lipid content. Cheese and Antarctica isolates were tested about their oil accumulation capacity from raw glycerol. UFMG-CM-Y6189 presented the best results, being capable of producing 9,40 g.L-1 of biomass, 1,90 g.L-1 of lipid yield and 21,56% of lipid content, from the consume of 61,3 g.L-1 of glycerol. The fatty acid present in the lipids were mostly monounsaturated (59,5%), and oleic acid was predominant (49,4%). These two features together with the low polyunsaturated content (5,2%) are desirable in the production of quality biodiesel. Therefore, lipids from the isolate Y. lipolytica UFMG-CM-Y6189 are potential feedstock for the biodiesel production from glycerol.